The Authority Of Midwives In Complementary Traditional Health Services Reviewed From Basics Of Legal Certainty - Asih, Lies Ratna (Fakultas Hukum, Universitas Islam Bandung, 2023)
ABSTRACTMidwifery services are the application of obstetrics science through midwifery care to clients that are the responsibility of midwives, ranging from pregnancy, childbirth, childbed, newborns, family planning, including women's reproductive health, complementary care and public health services. In this study the authors used a normative juridical approach. Research Specifications, this research is analytical descriptive. the type of data used is secondary data. Data collected through the study of literature (Library Research) of secondary data. The data obtained in this study were analyzed using qualitative normative methods. The results of this study are: First, the authority of midwives in traditional services of complementary therapy in carrying out midwifery practices both in the Midwife's Independent Practice or in other Health Care Facilities, must be carried out in according to competence and authority and adhere with ethical codes, professional standards, professional service standards and standard operating procedures.